Studying Comments in New York Times Magazine as Enhancement of English Language Skills - Yuliastuti, Anicleta; Pujimahanani, Cahyaningsih; Pasopati, Rommel Utungga (Lingua Franca, 2022)
Online comments in New York Times Magazine are open; people could agree, add up, debate, and even deny provided news and opinions. Studying the comments may also bring in a better experience for learners in how to speak their minds publicly. This study aims to explain useful matters of studying online comments in New York Times Magazine that could enhance language skills. Certain written data, concepts, and theories are explained further by asserting the qualitative method. Concepts of educational technology and customization of learning experiences are stated forward in line with the purpose of language education. The result of this study is that studying the comments is useful for language learners due to their closer relations to them in everyday life experiences. The news and comments are also up to date, so learners may know newer conditions outside. The vocabulary and grammar used are common and usual, so they could be consumed easily. Moreover, it is stated in conclusion that while the news and opinions provided by the magazine are formal, the comments are informal. Studying the comments also shows informal points of teaching language more familiar to learners.